Beyond Auschwitz - Morgan, Michael L. (Oxford University Press, 2001)
To this day Jewish thinkers struggle to articulate the appropriate response to the unprecedented catastrophe of the Holocaust. Here, Morgan offers the first comprehensive overview of Post-Holocaust Jewish theology, quoting extensively from and interpreting all of the significant American writings of the movement. Morgan's lucid analysis clarifies the background of the movement in the postwar period, its origins, its character, and its legacy for subsequent thinking, theological and otherwise. Ultimately, Morgan's primary purpose is to tell the story of the movement, to illuminate its real, deep point, and to demonstrate its continuing relevance today.